(untitled) (Research, Society and Development, 2021)
The present work is based on the hypothesis that the cultivation of different vegetation coverings could suppress the weed seed bank, in addition to improving soil conditions and increasing productivity. The objective of this work was to evaluate the weed seed bank with different vegetation cover. The experimental design used was in randomized blocks with nine treatments and four replications. The treatments consisted of vegetable coverings: crotalaria (Crotalaria juncea), millet (Pennisetum americanum), forage turnip (Raphanus sativus), sorghum (Sorghum bicolor), Urochloa brizantha, U. piatã, U. ruziziensis, seed mixture (forage turnip + millet) and fallow. The germinative flow of weeds was evaluated from soil samples, taken from the areas where the treatments were sown and taken to the greenhouse, where the quantification and identification of germinated weed seeds was carried out. The families Asteraceae, Convolvulaceae and Fabaceae stood out with the highest number of vegetation coverings. The use of plant coverings reduces the emergence of weeds from the seed bank. The turnip, turnip + millet and U. piatã coverings were the ones that most reduced the germination flow of weeds, while fallow, crotalaria and Urochloa ruziziensis had less capacity to reduce this flow.